Effect of 4-Allyl-2-Methoxyphenol (Eugenol) on Motor Co-Ordination in Subacute Restraint Stress Induced Wistar Albino Rats - Pandian Selvan, Malathi, Ravindran Rajan (Journal of Applied Pharmaceutical Science, 2016)
Eugenol is an allylbenzene class of chemical compounds, used in cosmetic and food products. Being a pro-oxidant and as an anti-oxidant, used as an essential component of many medicinal herbs. For years, it has been used in dental practice to relieve pain arising from pulpitis and dentinal hypersensitivity. There are few reports of anticonvulsant effect, but further effects are less reported. Lack of comprehensive studies and data of eugenol on the central nervous system effects in animal model thus necessitates further research activities. The aim of this study was to observe and evaluate the effect of eugenol on motor coordination in restraint stress induced rats. Animals were divided into five groups of six animals each. The group I Negative control (Unstressed, untreated), Group II Positive control (received vehicle PG), Group III treated with Eugenol (150 mg/kg B.W.), Group IV Restraint stress alone, Group V treated with Eugenol and restraint stress (150 mg/kg B.W.), The treatment was given for 15 days at the end of the 15th day plasma corticosterone and rota rod, narrow beam walk and stair case behavioural parameters have been measured. Significant effects of motor co-ordination were observed in treated and treated with stress group when compared to positive control groups. This study shows eugenol to possess improved motor coordination in immobilization stress induced Wistar rats.
Keywords: Eugenol, Wistar albino rats, Immobilization stress, Rota rod, Staircase, Narrow beam.